Model Dispute Resolution Nomination in the Election of the Governor, Regents and Mayors the Pursuit of Democratic Elections - Erman I. Rahim (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
One of the stages who often generates dispute between participantselection and organizers of an election in stage nomination the election ofthe governor, regents and mayors is the determination of candidate coupleparticipants election. Candidate couple were disadvantaged and objectionson the decision general election commission provincial or general electioncommission districts and city given the chance to suing the determination ofthe decision. The authority dispute resolution nomination done by monitorselection and the judiciary administrative can affect stage election. Evenharmful candidate couple and organizers of election. The resolutions ofdisputes nomination the election of the governor, regents and mayors is aprerequisite to embodying an democratic. Building on the approach takenthe writing of law normative can be conducted the perfecting ketentuanketentuanwhich regulates regional with the resolution of disputes thecandidacy of in the election of the governor , regents and mayors .Keywords : A model , the candidacy of dispute , the election of the governor , the cardcan be used and democratic